Influencer marketing di Instagram: Apakah influencer type, brand familiarity dan sponsorship disclosure mempengaruhi purchase intention - Susilowati, Heni; Ady, Pangeran Pandu Bayu; Widyaningsih, Dewi (Nur Science Institute, 2024)
Influencer Marketing has changed the way people communicate, interact and engage with each other through social media. Influencers are considered to have the ability to spread information about a product by sharing sponsored content and brand messages so that consumers intend to buy. This research aims to determine the factors that influence the purchasing intentions of Surakarta people on Instagram. The sample selected was 100 respondents domiciled in Surakarta who actively use Instagram. The sampling technique uses nonprobability sampling with an incidental sampling method. Data were collected by distributing a questionnaire consisting of 20 question indicators via Instagram stories; then, the data was measured using a 1-5 Likert scale and processed using Multiple Linear Regression analysis. The findings showed that the variables influencer type, brand familiarity, and sponsorship disclosure are factors that influence the purchasing intentions of Instagram users in Surakarta. Social Media Influencers such as Instagram have an effective impact on marketing strategies.